(untitled) (Global Journal of Human-Social Science, 2021)
Energy consumption, economic growth, and climate change are the three vertices of the ’energy trilemma’ of the Indian economy. In the path of development, India has the challenge to produce energy and mitigate carbon emissions maintaining a pace of development of society, economy, and ecology, holistically known as sustainable development. The present study analyses the adoption and promotion of renewable energy and technology in India from an economic and sustainability perspective using qualitative and quantitative frameworks and empirical data. Correlation analysis of growth indicators reveals the increased contribution of renewable energy in the nation’s energy and electricity access to nationals’ tread in tandem. The time series trend of India’s growth indicators supports the argument that renewable energy not only contributes to the mitigation of carbon emission but also strengthens the economic growth by inviting investments, enhancing the trade basket, and generating employment opportunities.